Economia solidária : princípios e contradições - Amorim, Andressa Nunes (2010)
The purpose of this essay is to analyze whether atypical social relations of solidarity economy converge for structuring a new mode of capitalist production. For this the methodological procedure used was the bibliography search books, journals, theses, dissertations, collections of texts, plus data from official institutions like the Ministry of labour and Employment and the Brazilian Institute of geography and statistics. Thus, empirical study of the European cooperative movement of the 19th century and its relationship with the emergence of solidarity economy in Brazil, besides the presentation of the various theoretical conceptions of solidarity economy marked by inaccuracies and incompletudes, passing by the contradictions of the guiding principles of self-management, solidarity and action, its relationship with the third sector. From this set of elements passed to the analysis of economic solidarity as a means of structuring a new mode of capitalist production, its limitations and potential of solidarity economy training policy and construction of a new sociability. It was noted that, throughout the 1990s and, in particular during the years 2000, there was an explosion of new groups of solidarity economy in Brazil, arising as a consequence of structural employment crisis, caused by the need to increase return on capital. In this scenario inspired by principles of solidarity and economic solidarity enterprises self-management experience conflicting relations is facing its own principles, whether through close liaison with the third sector through the Advisory and promotion entities, whether for the defence of a proposal anticapitalista combined with the experience in the market economy. This is an analysis that considers the limits and possibilities of solidarity economy from its contradictions and its potentiality as systemic transformation engine.